2017
DOI: 10.18632/oncotarget.18649
|View full text |Cite
|
Sign up to set email alerts
|

Silencing protein kinase C ζ by microRNA-25-5p activates AMPK signaling and inhibits colorectal cancer cell proliferation

Abstract: Developing novel strategies against human colorectal cancer (CRC) cells is needed. Activation of AMP-activated protein kinase (AMPK) could possibly inhibit CRC cells. Protein kinase C ζ (PKCζ) is an AMPK negative regulator. Here we found that PKCζ expression was significantly elevated in human colon cancer tissues and CRC cells. PKCζ upregulation was correlated with AMPK in-activation and mTOR complex 1 (mTORC1) over-activation. Reversely, PKCζ shRNA knockdown activated AMPK signaling and inhibited HT-29 cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…miR-574-5p also participates in the promotion of metastasis and invasion of lung cancer through PTPRU (protein tyrosine phosphatase, receptor type U) [ 35 , 36 ] and TLR9 signaling [ 37 ]. In addition, miR-25-5p has been shown to inhibit cell proliferation of colorectal cancer through activation of AMP-activated protein kinase (AMPK) signaling by silencing protein kinase C ζ [ 38 ], suggesting that sequestering of miR-25-5p activates cancer cell proliferation and affects regulation of energy metabolism and maintenance of glucose homeostasis mediated by AMPK signaling [ 39 ]. Further studies are needed to clarify the roles of sequestration of miRNAs such as miR-574-5p and miR-25-5p by the replication of HCV in the development of extrahepatic manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…miR-574-5p also participates in the promotion of metastasis and invasion of lung cancer through PTPRU (protein tyrosine phosphatase, receptor type U) [ 35 , 36 ] and TLR9 signaling [ 37 ]. In addition, miR-25-5p has been shown to inhibit cell proliferation of colorectal cancer through activation of AMP-activated protein kinase (AMPK) signaling by silencing protein kinase C ζ [ 38 ], suggesting that sequestering of miR-25-5p activates cancer cell proliferation and affects regulation of energy metabolism and maintenance of glucose homeostasis mediated by AMPK signaling [ 39 ]. Further studies are needed to clarify the roles of sequestration of miRNAs such as miR-574-5p and miR-25-5p by the replication of HCV in the development of extrahepatic manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Another dysregulated miRNA found in our study was miR-25, which was found to be markedly upregulated in CHD patients with HF. MiR-25 belongs to the miR-106b-25 cluster; it is located on chromosome 7q22.1 and contributes to various pathological processes that are mostly related to cancers and diseases like diabetic nephropathy ( 25 - 27 ). Interestingly, miR-25 is also reported to be involved in the pathogenesis of HF.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that some miRNAs are critically involved in MLT-induced apoptosis in several cancers, such as breast [31] and colon cancers [32]. Among them, though miR-25 was known to promote proliferation in several cancers, such as lung cancer [33], prostate cancer [34], ovarian cancer [35], and colorectal cancer [36] as an oncogene, miR-25-5p was reported to suppress PKCζ as a tumor suppressor [37,38]. Also, among several target molecules, neural precursor cell expressed developmentally downregulated 9 (NEDD9), so called Cas-L (Crk-associated substrate L) or human enhancer of filamentation1 (HEF1), promotes proliferation [39] and metastasis [19,39] in breast cancer, colorectal cancer, and head and neck cancer [40,41].…”
Section: Introductionmentioning
confidence: 99%